Operating System Realization for Real-Time Visualization of CAN-Bus Data Streams using Xilinx Zync SoC - Zedan, Mohammad J. M. (Journal of Electrical, Electronics and Informatics; Vol 4 No 2 (2020): JEEI (August 2020)DO - 10.24843/JEEI.2020.v04.i02.p02, 2020)
The revolution in the automotive industry over time led to more and more electronics to be included in the vehicle and this increased the number and space allocated for cables. Therefore, the in-vehicle cabling network has been replaced with a two-wire bus serial communications protocol called Controller Area Network (CAN). The proposed paper describes the implementation of the CAN controller as a listener to monitor the state of the CAN bus in a real-time approach. The CAN listener obtains the data from the CAN bus by using an external signals converter. The work is realized using development platform called ZedBoard. The controller performs a sequence of processes on the received CAN frames including decoding, buffering and filtering. The processed data is stored in an implemented FIFO to keep the data from loss. After that, the data is sent serially to the processor system over the implemented SPI that connects the controller with the processor of the Zynq-7000 device. A single-threaded, simple operating system is run over the processor to provide a set of libraries and drivers that are utilized to access specific processor functions. It enables the execution of the C code that was written to configure the operation of the onboard display unit. The design procedure and simulation process for the implemented CAN listener is achieved using the Xilinx ISE WebPACK environment, while the final complete design is properly tested and verified by connecting the module to a CAN network consisting of six CAN nodes.